The Legal Construction of Guardianship in Relation to the Temporary Suspension of Notaries: An Analysis of Article 9 Paragraph (1) Letter b of Law Number 2 of 2014 - Fara Jane; Mella Ismelina Farma Rahayu (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the regulation of guardianship in Article 9 paragraph (1) letter b of Law Number 2 of 2014 concerning the Position of Notaries is designed to ensure that notaries possess adequate mental and professional capacity before performing their duties or being temporarily suspended. However, in reality, a normative gap exists: the definition of guardianship still relies on classical civil law, independent medical verification guidelines are absent, and administrative procedures are often subjective, risking violations of administrative justice principles. This study aims to analyze the legal construction of guardianship and to formulate a new interpretative model that integrates legal perspectives, administrative practices, and evidence-based decision medical verification. The study employs a qualitative library research methodology. Primary sources include the Notary Law, Civil Code, and legal doctrines, while secondary sources consist of scientific journals, policy reports, and contemporary psychiatric literature. Data analysis was conducted through content analysis and comparative methods, validated using literature triangulation. The findings suggest that guardianship should be assessed based on contextual functional capacity rather than normative status, allowing temporary suspension to be applied fairly, proportionally, and based on evidence, thereby enhancing the legitimacy of the Notary Law and protecting the notary profession.